Short-term heart rate recovery is related to aerobic fitness in elite intermittent sport athletes - Watson, A. M.; Brickson, S. L.; Prawda, E. R.; Sanfilippo, J. L. (The Journal of Strength and Conditioning Research, 2017)
Although heart rate recovery (HRR) has been suggested as a measure of fitness, minimal data exist among athletes. The purpose of this study was to determine if HRR is related to aerobic fitness in elite athletes and whether this relationship is influenced by sex or body composition. Eighty-four collegiate athletes (45 male athletes) underwent body fat percentage (BF%) determination by dual-energy x-ray absorptiometry and maximal treadmill testing followed by 5 minutes of recovery. VO2max and heart rate (HRmax) were determined, and HRR was calculated as a percentage of HRmax at 10 seconds, 30 seconds, and 1, 2, 3, 4, and 5 minutes after test completion. After stratifying by sex, participants were grouped as high fit or low fit based on VO2max median split. Heart rate recovery was compared between sexes and fitness level at each time point. Multivariable regression analysis was used to identify independent predictors of HRR using VO2max, BF%, and sex as covariates. Heart rate recovery did not differ significantly between sexes and was faster among high-fit participants at 10 and 30 seconds, but at no other time. VO2max was significantly correlated with HRR at 10 and 30 seconds (r = -0.34, p < 0.001 and r = -0.28, p = 0.008) only. After controlling for BF% and sex, VO2max remained significantly associated with HRR at 10 seconds (p = 0.007) but not at 30 seconds (p = 0.067) or any time thereafter. Aerobic capacity is related to faster HRR during the first 30 seconds only, suggesting that only very short term HRR should be used as a measure of aerobic fitness in intermittent sport athletes.